PROTECTIVE MODULATORY POTENTIAL OF AZOLLA PINNATA EXTRACT ON LIPID METABOLISM, HEPATIC DYSFUNCTIONING, ALONG WITH MITIGATION OF OXIDATIVE STRESS IN TRITON X-100 INDUCED HYPERLIPIDEMIC RATS - MADAN L. KAUSHIK; SHAVINDER KUMARI; MAHENDRA SINGH ASHAWAT (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective of the study was to investigate the hypolipidemic and antioxidant effects of ethanolic extract of Azolla pinnata (EEAP) in Triton X-100-induced hyperlipidemic rats. Methods: Hyperlipidemia was induced in male Wistar rats (n=6/group) by intraperitoneal injection of Triton X-100 (100 mg/kg). Animals were divided into five groups: normal control, Triton control, EEAP 125 mg/kg, EEAP 250 mg/kg, and atorvastatin 10 mg/kg. EEAP was prepared by Soxhlet extraction (yield: 17.2%) and screened for phytochemicals. Antioxidant potential was evaluated using 1,2-diphenyl-2-picryl-hydroxyl radical (DPPH) and nitric oxide scavenging assays. After 7 days of treatment, serum lipid profile, liver and kidney function markers (alanine aminotransferase, aspartate aminotransferase, bilirubin, creatinine, blood urea nitrogen), oxidative stress markers (thiobarbituric acid-reactive substances [TBARS], malondialdehyde [MDA], glutathione [GSH]), and liver histology were analyzed. Data were statistically analyzed using Analysis of Variance followed by Tukey’s multiple comparison test. Results: EEAP showed moderate antioxidant activity (DPPH IC50=379.17 μg/mL, and NO IC50=113.9314 μg/mL) and significantly improved lipid profile by lowering triglyceride (136.18±1.04), total cholesterol (117.18±1.20), low-density lipoprotein (139.12±2.10), and very low-density lipoprotein (48.94±1.20), ***p<0.001 while increasing high-density lipoprotein (33.28±1.10 mg/dL; ***p<0.001). It normalized hepatic markers and reduced TBARS and MDA, with increased GSH. Liver histology showed improved architecture, especially at 250 mg/kg. Conclusion: A. pinnata, a flavonoid and phenolic-rich aquatic fern, remains insufficiently studied for its potential in hyperlipidemia and oxidative stress management. EEAP exerted significant lipid-lowering and antioxidant effects in hyperlipidemic rats, indicating its potential as a natural therapeutic agent for hyperlipidemia and oxidative stress.